Technology development, application and prospect of cellular vehicle-to-everything (C-V2X) - Shanzhi CHEN; Yuming GE; Yan SHI (Dianxin kexue)
V2X (vehicle-to-everything) is a promote and profound reform-and-innovation in transportation and automobile industries.It is changing the people’s travel mobility modes and ways of society energy consumption.The requirements and challenges of V2X communication performance in data rate, latency, and reliability, being required and challenged by intelligent transportation and automated driving applications were analyzed.The critical technologies and international standards evolutions of cellular vehicle-to-everything (C-V2X) were introduced, including LTE-V2X and NR-V2X.Then, the advantages of applying C-V2X were analyzed for vehicle-vehicle and vehicle-infrastructure cooperation in intelligent transportation and automated driving.Meanwhile, the field testing and industrial practice of C-V2X in China were presented, and the roadmap was envisioned for developing intelligent transportation and intelligent connected vehicles (ICV) in China.For example, the envisions include actively promoting the construction of “5G+C-V2X” and new type infrastructure, exploring the development mode of vehicle-infrastructure cooperation based on V2X, and eventually supporting China to reach the national low “carbon peak” and to achieve the national “carbon neutralization” strategic goals.